Interaction between the Cesium Cation and Cesium Carboxylates: An Extended Cs+ Basicity Scale. Issue 9 (26th August 2013) - Mayeux, Charly; Tammiku‐Taul, Jaana; Massi, Lionel; Gal, Jean‐François; Burk, Peeter
Abstract: The interaction between the cesium cation and fulvic or humic acids is supposed to play a role in cesium mobility in the environment, which is of importance in the context of geographical dispersion or concentration of the corresponding radionuclides. Among the singly charged positive clusters generated by electrospray ionization of mixtures of carboxylic acids (AH) and cesium salts (nitrate, iodide, or trifluoroacetate), the cluster [A − Cs + ]Cs + [A′ − Cs + ] was subjected to collision‐induced dissociation. The fragmentation into Cs + [A − Cs + ] and Cs + [A′ − Cs + ] was treated using the kinetic method. A gas‐phase basicity ladder was built by a step‐by‐step addition of the relative basicity data. The relative basicity scale deduced from the kinetic method was calibrated using the affinity and basicity (the enthalpy and Gibbs energy scales, respectively) obtained from DFT calculations. The enhanced basicity of the polyacid salts, relative to their monoacid salts, as well as the substituent effects on aliphatic and aromatic structures, are discussed. Abstract : A step up : A gas‐phase Cs + affinity/basicity scale using the kinetic method and DFT calculations has been generated (see figure).The basicity scale was built step‐by‐step by combining the experimental basicity intervals and checking the internal consistency from overlapping measurements. The experimental scale was validated and calibrated by means of enthalpies calculated by density functional theory and Gibbs energies.